2011
DOI: 10.1002/bem.20695
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency electromagnetic fields do not alter responses of inflammatory genes and proteins in human monocytes and immune cell lines

Abstract: The effects of low frequency electromagnetic fields (LF EMF) on human health are the subject of on-going research and serious public concern. These fields potentially elicit small effects that have been proposed to have consequences, either positive or negative, for biological systems. To reveal potentially weak but biologically relevant effects, we chose to extensively examine exposure of immune cells to two different signals, namely a complex multiple waveform field, and a 50 Hz sine wave. These immune cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
18
3
Order By: Relevance
“…All investigated genes did show a small dynamic regulation of gene expression levels during neutrophil differentiation, ranging from a 0.5 decrease for IP3 receptor up to 4.5 fold increase for β‐actin in our cell line. Genes investigated in our study were not previously reported in combination with LF EMF exposure, but current results are in line with cytokine gene expression in macrophages [Bouwens et al, ], NF‐kB induction in monocytes [Miller et al, ], and heat shock protein 70 expression in neutrophil‐like cells [Morehouse and Owen, ; Jorquera et al, ]. They also showed no significant effect of LF EMF on expression patterns of cell‐specific secondary genes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All investigated genes did show a small dynamic regulation of gene expression levels during neutrophil differentiation, ranging from a 0.5 decrease for IP3 receptor up to 4.5 fold increase for β‐actin in our cell line. Genes investigated in our study were not previously reported in combination with LF EMF exposure, but current results are in line with cytokine gene expression in macrophages [Bouwens et al, ], NF‐kB induction in monocytes [Miller et al, ], and heat shock protein 70 expression in neutrophil‐like cells [Morehouse and Owen, ; Jorquera et al, ]. They also showed no significant effect of LF EMF on expression patterns of cell‐specific secondary genes.…”
Section: Discussionsupporting
confidence: 90%
“…Since EMF characteristics may be crucial to determine a biological response [Pilla et al, ], we focused on two LF EMF signals: a 50 Hz sine wave, which resembles the household alternating current (AC) electrical power supply in a large part of the world; and a signal named Immunent, which represents an irregular combination of multiple frequencies. LF EMF Immunent exposure has previously been reported to improve growth and resistance in goldfish and chickens [Cuppen et al, ], but was unable to influence cytokine gene expression in immune cells [de Kleijn et al, ; Bouwens et al, ]. The irregular combination of frequencies from the Immunent signal shows resemblance to dirty power or dirty electricity.…”
Section: Introductionmentioning
confidence: 99%
“…The signal V ( t ) applied to the coil was described previously [Bouwens et al, 2012] and is the sum of 4 simultaneously generated square wave signals with equal amplitudes and periodicities f i  = 401, 432, 700, and 750 Hz, respectively. As mentioned in the introduction, steep ramps and sharp corner peaks in square wave signals could be considered to mimic effects of “dirty electricity” power nets.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there are indications that production of reactive oxygen species and inflammatory cytokines under exposure to 50 Hz ELF‐EMF is increased [Petrini et al, 1997; Frahm et al, 2009; Patruno et al, 2009]. However, these results are in contrast with studies that could not find any effects [Ikeda et al, 2003; de Kleijn et al, 2011; Bouwens et al, 2012]. It is therefore still being called into question whether ELF‐EMF exposure can induce changes at cellular level and more importantly, that these changes have direct consequences for human health.…”
Section: Introductionmentioning
confidence: 97%
“…An irregular combination of four block waves, described previously [16], with frequencies of 320, 730, 880 and 2,600 Hz was applied at a magnetic field intensity of 300 µT. Sham treatment consisted of identical culture conditions with a unenergised coil in a second identical incubator.…”
Section: Methodsmentioning
confidence: 99%